Neuroparsin 1 (MrNP1) and Neuroparsin 2 (MrNP2) Are Involved in the Regulation of Vitellogenesis in the Shrimp Macrobrachium rosenbergii - Ao, Chun Mei; Shi, Li Li; Wang, Wei; Wang, Cheng Gui; Chan, Siuming F. (Frontiers in Marine Science, 2022)
Neuroparsins (NP) are small-size cysteine-rich neuropeptides first discovered in insects. They are known to be involved in insect reproduction. In this study, we have cloned two neuroparsin cDNAs (i.e., MrNP1 and MrNP2) from the freshwater shrimp Macrobrachium rosenbergii. The two neuroparsins consist of 12 cysteines, which is characteristic of the neuroparsin family. These cysteines are arranged in identical relative positions that form 6-disulfide bonds. MrNP1 and MrNP2 are most similar to the corresponding neuroparsin counterparts of the shrimp Macrobrachium nipponense. Phylogenetic study results suggested that MrNP1 and MrNP2 are closely related to MnNP1 and MnNP3, respectively. Also, an additional MrNP gene similar to MnNP2 is expected to exist in M. rosenbergii. The MrNP1 expression level is the highest in the ovary, and MrNP2 expression is higher in the brain and heart of the females. In addition, during the ovary maturation cycle, MrNP1 expression in the hepatopancreas is highest in stage V; in the ovary it is variable. MrNP2 expression in the hepatopancreas and ovary is the highest in stage II and stage I, respectively. In vivo and in vitro bioassay experiment results indicate that MrNP1 and MrNP2 recombinant proteins can stimulate the expression of the MrVg gene. In contrast, silencing of MrNP1 and MrNP2 genes would suppress MrVg, VgR, and CyclinB gene expressions. The results indicate that the products of both genes can stimulate vitellogenesis by up-regulating the MrVg gene expression. Results from their difference in expression patterns indicate that they might have different regulatory roles in vitellogenin synthesis. Since gene silencing of either MrNP1 or MrNP2 affected the expression of the other NP, we have hypothesized that coordinated regulatory action between MrNP1 and MrNP2 may be necessary for the normal vitellogenesis in M. rosenbergii.